Impact of red blood cell transfusion on platelet activation and aggregation in healthy volunteers: results of the TRANSFUSION study - Silvain, Johanne; Pena, Ana; Cayla, Guillaume; Brieger, David; Bellemain-Appaix, Anne; Chastre, Thomas; Vignalou, Jean-Baptiste; Beygui, Farzin; Barthelemy, Olivier; Collet, Jean-Philippe; Montalescot, Gilles (European heart journal, 2010)
Aims The underlying mechanisms leading to recurrent ischaemic events or mortality after red blood cell (RBC) transfusion in anaemic acute coronary syndrome patients are poorly understood. The aim of this paper is to determine whether RBC transfusion increases platelet activation and aggregation. Methods and results In vitro transfusions (n = 45) were performed by the addition of RBCs obtained from transfusion packs to fresh whole blood provided by healthy volunteers. Residual platelet aggregation (RPA) and maximal platelet aggregation (MPA) were assessed before and after in vitro transfusion using light transmission aggregometry performed with four different agonists. Flow cytometry was used for the measurement of P-selectin expression and vasodilatator-stimulated phosphoprotein (VASP) platelet reactivity index (PRI). To control for the effect of haemoconcentration, the same experiments were repeated after hematocrit adjustment using volunteer's platelet poor plasma. Transfusion increased platelet aggregation as measured by RPA with ADP 5 µM (57.7 ± 25 vs. 65.7 ± 24%; P = 0.03) or Collagen 2 µg/mL (59.4 ± 28 vs. 69.7 ± 24%; P = 0.03). There were no significant differences with Arachidonic Acid 1.25 mM or Epinephrine 20 µM and results were similar when MPA was considered. Platelet activation was also increased by transfusion as confirmed by an elevation of P-selectin expression induced by 20 µM ADP (12.2 ± 18 vs. 23.9 ± 18%; P = 0.002) or 50 µM ADP (15.4 ± 18.6 vs.26.8 ± 21.2%; P = 0.004) and an increase in VASP PRI (77.8 ± 6 vs. 81.9 ± 3%; P = 0.03). These effects were all independent of hematocrit. Conclusion Red blood cell transfusion increases platelet activation and aggregation in vitro in healthy volunteers. This effect might be mediated through the P2Y12 activation pathway.